Effectiveness of estradiol valerate on sex reversion in Astyanax altiparanae (Characiformes, Characidae) - Bem, Jaqueline Cristina de [UNESP]; Fontanetti, Carmem Silvia [UNESP]; Senhorini, José Augusto; Parise-Maltempi, Patricia Pasquali [UNESP] (Brazilian Archives of Biology and Technology, 2012)
The objective of this study was to evaluate the effectiveness of estradiol valerate in an attempt to feminize the male Astyanax altiparanae. One thousand newly-hatched larvae were randomly distributed in four incubators. During a period of 30 days, estradiol valerate was administered in different dosages (20, 40, and 80 mg/kg of diet); the control group did not receive hormone in the diet. After 161 days of hatching, biometry was performed on 50 fishes per treatment group, and the gonads were analyzed. The hormone treatments were effective in feminizing A. altiparanae, achieving 70-76% of the desired sex, while the control treatment had 44% females. The hormone did not affect the growth of fish.
Keywords: Astyanax altiparanae; Characidae; Feminization; Sex Reversion; Estrogen